Ormdl3 regulation of specific ceramides is dispensable for mouse β-cell function and glucose homeostasis under obesogenic conditions - Hurley, Liam D.; Lee, Hugo; Wade, Gina; Simcox, Judith; Engin, Feyza (Frontiers in Endocrinology, 2023)
Chronic elevation of sphingolipids contributes to β-cell failure. ORMDL3 has been identified as a key regulator of sphingolipid homeostasis, however, its function in pancreatic β-cell pathophysiology remains unclear. Here, we generated a mouse model lacking Ormdl3 within pancreatic β-cells (Ormdl3β-/-). We show that loss of β-cell Ormdl3 does not alter glucose tolerance, insulin sensitivity, insulin secretion, islet morphology, or cellular ceramide levels on standard chow diet. When challenged with a high fat diet, while Ormdl3β-/- mice did not exhibit any alteration in metabolic parameters or islet architecture, lipidomics analysis revealed significantly higher levels of very long chain ceramides in their islets. Taken together, our results reveal that loss of Ormdl3 alone is not sufficient to impinge upon β-cell function or whole-body glucose and insulin homeostasis, however, β-cell-specific loss of Ormdl3 does significantly alter levels of specific sphingolipid species in islets upon high fat feeding.